Education in a digital world : global perspectives on technology and education - Selwyn, Neil. (Routledge, 2013)
"The book takes a comprehensive look at digital technology use in educational settings around the world. Drawing on a wealth of theoretical and empirical work, the book tackles a number of pressing questions"--